The influence of selected exercise on plasma levels of testosterone and cortisol during preparation and competitive period in semi-endurance elite runners - Hejazi, K.; Nikroo, H.; Attarzadeh Hosseini, S. R. (Journal of Physical Education and Sport, 2012)
High-intensity exercises cause changes in levels of Anabolic and Catabolic Serum Hormones. The aim of this paper is to study the reaction of Testosterone and Cortisol hormones and thus Testosterone to Cortisol concentration ratio (the ratio of T/C) in semi endurance elite male runners during training period. Thirteen semiendurance elite male runners with an average age of 18.92 +/- years and Body Mass Index of 20.07 +/-1.50 kilograms per square centimeter were selected through selective sampling. The runners participated in the selected exercise program for fourteen weeks consisting of twelve sessions a week (in the morning and afternoon). Serum Testosterone and Cortisol were measured through Immunoradiometric Assay by means of a Gamma Counter before and after the general training period. Collected data were first tested by Kolmogorov-Smirnov test to ensure their normal distribution within a significance level of P.0.05 and then examined by statistical T-Student test in dependent groups. The results show that the general training period has a significant effect on decrease of serum Cortisol (P<0/05). The levels of serum Testosterone and Cortisol concentration ratio also increase but not significant. Selected training, improved procedure of the anabolic process. Although, variations of testosterone cortisol ratio mention to the anabolic compatibility that it caused by regular training. So, these training in to the preparation phase caused to improve of the athletic elite performance and it useful to the coaches and athletic.